Prognostic significance of competition ratios in surgical specialty training selection. Issue 1163 (16th June 2021) - Mellor, Katie; Robinson, David B; Luton, Oliver; James, Osian P; Powell, Arfon GMT; Hopkins, Luke; Hemington-Gorse, Sarah; Egan, Richard J; Lewis, Wyn G
Abstract : Background: A competition ratio (CR) indicates the ratio of total applications for a training post when compared with numbers of specialty posts available. This study aimed to evaluate CRs' influence on National Training Number (NTN) selection in a single UK Statutory Education Body. Methods: Consecutive core surgical trainees numbering 154 (105 men, 49 women; median years since graduation: four) were studied over a 6-year period. Annual specialty specific CRs were obtained from Health Education England's website, and primary outcome measure was UK NTN appointment. Results: Overall NTN appointment was 45.5%. Median CR was 2.36; range Oral & Maxillofacial Surgery 0.70 (2020) to Neurosurgery 22.0 (2020). Multivariable analysis revealed that NTN success was associated with: CR (OR 0.46, p=0.003), a single scientific publication (OR 6.25, p=0.001), cohort year (2019, OR 12.65, p=0.003) and Universal Annual Review of Competence Progression Outcome 1 (OR 45.24, p<0.001). CRs predicted NTN appointment with a Youden index defined critical ratio of 4.42; 28.6% (n=8) versus 49.2% (n=62), p=0.018. Conclusion: CRs displayed 30-fold variation, with CRs below 4.42 associated with twofold better NTN promotion, but strong clinical competence and academic reach again emerged as the principal drivers of career advancement.